Eccentric development of Balo's concentric sclerosis: detected by magnetic resonance diffusion-weighted imaging and magnetic resonance spectroscopy. (1st June 2015) - Chen, Feng; Liu, Tao; Li, Jianjun; Xing, Zengbao; Huang, Shixiong; Wen, Guoqiang; Lu, Guangming
<x xml:space="preserve">Abstract</x> Background: The concentricity of BCS has captured wide attention; the findings of the current study may provide useful information on the centrifugal pathogenesis of BCS. Objective: This study aims to evaluate the performance of MRI, DWI and MRS in elucidating the pathogenesis of Balo's lesions expanding. Methods: Six clinically diagnosed BCS cases were reviewed, and the findings obtained by MRI, DWI and MRS were analyzed. DWI data were available for six patients, with the DWI and ADC imaging locations being central and peripheral layers of the index lesion. At TE 144ms, we calculated metabolite ratios of MRS at different depths of the demyelinating lesions and compared with the lesion on the opposite normal side for two patients. Results: The ADC values of 18 typical concentric lesions revealed that the central lesion had the highest ADC value, followed by the internal ring, and the outermost layer had the lowest ADC value. The reduction in NAA/Cr and the increase in Cho/Cr were more evident in the central lesion than in the internal and outermost ring. Conclusion: The findings of DWI and MRS indicate Balo's concentric rings develop gradually and centrifugally. Of course, this hypothesis remains to be proved by further experimental studies.